Flow-Injection Chemiluminescence Determination of Ceftezole Sodium Based on its Enhancing Effect on Luminol-Potassium Ferricyanide System - Wang, Ruiqiang; Wang, Rui; Xie, Yuanzhe; Wang, Yi; Pu, Juan-Juan; Lin, Cuiping; Li, Qiang; Li, Zhigang; Wang, Ruiyong (Asian Journal of Chemistry, 2013)
A new chemiluminescence method coupled with the flow injection technique for the determination of ceftezole sodium is developed. It is based on the enhancement of ceftezole sodium on the chemiluminescence intensity of luminol-potassium ferricyanide system in sodium hydroxide medium. This method has the advantages of high sensitivity, wide linear range, low detection limit, good reproducibility and simple instrument. Under the optimum conditions, the relative chemiluminescence intensity is proportional with the concentration of ceftezole sodium in the range of 1.0 × 10-7 to 1.0 × 10-4 g mL-1. The limit of detection is 3.0 × 10-8 g mL-1 and the relative standard deviation for 11 parallel measurements of 7.0 × 10-6 g mL-1 ceftezole sodium is 1.6 %. The proposed method has been applied to the determination of ceftezole sodium in synthetic and real samples with satisfactory results.